Determinants of the Behavioural Intentions of Households to Recycle E-Waste in Sri Lanka - Deyshappriya , N.P Ravindra; Kumari , M.M.T.D.M (Asian Journal of Empirical Research, 2019)
This study seeks to recognize the determinants of behavioural intentions of households to recycle e-waste (ER = e-waste recycling) in Sri Lanka. Structural equation modelling was applied to analyse the data of 230 households. The measurement model confirmed the appropriateness of the considered constructs and variables to estimate statistical relationships among the recognized variables. The structural model emphasized that factors such as environmental awareness, attitude to recycling, social pressure, and rules and regulations positively affect the behavioural intentions to recycle e-waste while the inconvenience and cost of recycling affect it negatively in Sri Lanka. Apart from that the moderating effect stresses that previous experience in ER reduces the inconvenience of recycling and therefore past experience of ER indirectly increases the perception of ER. This study also highlights that socio-economic factors such as education, age, household size, gender, and income significantly affect the behavioural intentions to recycle e-waste and the impact of these demographic factors varies across the urban, rural, and state sectors.